Comprehensive relationship between disease activity indices, mTSS, and mHAQ and physical function evaluation and QOL in females with rheumatoid arthritis - Tetsuyuki Nagafusa; Takashi Mizushima; Motohiro Suzuki; Katsuya Yamauchi (Scientific Reports, 2023)
Abstract Rheumatoid arthritis (RA) causes significant physical disability. We comprehensively investigated the relationship between RA disease activity (Disease Activity Score 28-C-reactive protein [DAS28-CRP], Simplified Disease Activity Index [SDAI], and Clinical Disease Activity Index [CDAI]), physical function (10-Meter Walk Test [10 MWT], Timed Up and Go test [TUG], Functional Reach Test [FRT], and Disabilities of the Arm, Shoulder, and Hand [DASH]), and quality of life (QOL) (Short-Form 36 [SF-36®]). We also investigated the relationship between van der Heijde’s modified Total Sharp Score (mTSS), modified Health Assessment Questionnaire (mHAQ), and physical function and QOL assessments. Among 35 female patients with RA, DAS28-CRP correlated solely with DASH (r = 0.376), while SDAI and CDAI did not correlate with physical function. The mTSS-hand roentgenographic evaluation correlated with TUG (r = 0.359), FRT (r = − 0.415), and DASH (r = 0.533) among physical function assessments. The mHAQ correlated with 10 MWT (r = 0.347), TUG (r = 0.356), FRT (r = − 0.420), and DASH (r = 0.646). DAS28-CRP correlated with six of the eight subscales of SF-36®, and mTSS and mHAQ correlated with only one subscale. RA disease activity assessments may not reflect all physical functions and QOL domains of female patients with RA. Evaluating physical function and QOL in female patients with RA is essential.